Method for Simultaneous Determination of Glutamine Synthetase and Adenosine Triphosphatase Activities on Polyacrylamide Gel - Nagy, A.H.; Csanadi, J; Turtoczky, I.; Gyurján, I.
A method for the simultaneous localization of adenosine triphosphatase and glutamine synthetase after non-denaturing polyacrylamide gel electrophoresis is described. The determination of enzyme aetivities is based on the staining for the inorganic phosphate produced by aetivities of both glutamine synthetase and adenosine triphosphatase enzymes. The speeificity of the glutamine synthetase reaction was demonstrated by methionine sulphoximine (MSO)inhibition of the enzyme reaction. Mg2+ -ATPase, Ca2+ -ATPase and glutamine synthetase enzymes were sneeesfully separated on a continuous linear (3-10 percent)polyacrylamide gradient. Glutamine synthetase and ATPase enzymes isolated from Azotobacter bejerinckii and from the green alga Chlamydomonas reinhardii showed different isoenzyme pattern after electrophoretic annlysis.
Keywords: GLUTAMINE SYNTHETASE; ADENOSINE TRIPHOSPHATASE; ACTIVITY IN GELS; CHLAMYDOMONAS REINHARDII; AZOTOBACTER BEJERINCKII